Synthesis and liquid crystalline properties of new triazine-based π-conjugated macromolecules with chiral side groups - Akkurt, Nihat; Al-Jumaili, Mohammed Hadi Ali; Ocak, Hale; Cakar, Fatih; Torun, Lokman (Tubitak Scientific & Technological Research Council Turkey, 2020)
In this study, we reported the synthesis of a new tribranched macromolecule liquid crystal with triazine in the centre. The central triazine core is bonded via sequences of Sonigashira coupling to 3 triazine unites through acetylenic bridges. The triazines at the periphery are substituted with 2 chiral citronellyloxy side groups. The salt of the resulting star-shaped macromolecule, which was oily at room temperature, with 4-dodecyloxybenzoic acid at 1:1 ratio exhibited a Smectic C (SmC) mesophase. The liquid crystalline properties of organic salt were investigated using DSC (differential scanning calorimetry) and POM (polarizing optical microscopy).
Keywords: Triazine; ionic liquid crystals; hydrogen bonding; star-shaped triazine; Sonogashira coupling; G PHASE; MOLECULES; MESOGENS; SERIES; Chemistry; Engineering